Continuous Teaching Practice of Prevention Education for the Internet Addiction and Gaming Disorder in Junior High-School and High-School - Tsuruta, Toshiro (Computer & Education, 2022)
The author developed a continuous program for preventing gaming disorder and internet addiction. One hundred twenty students participated in the program for four years from 2018 (in 8th grade) to 2021 (in 11th grade). The program included subjects such as special activities, information, health and physical education, science, and home economics. The students answered a questionnaire concerning internet addiction tendencies at four time points (prior to the start of the program, at the end of junior high, at the end of the program, and six months after the end of the program). The results showed students' internet addiction tendencies changed for the better, and time spent on games was reduced. This effect was maintained after program completion.